Cost Analysis in the Audit of Selected Companies in Poland - Anna Mazurczak-Mąka; Monika Turek-Radwan (Nauki o Finansach)
The aim of the article is to present the issues related to the work of auditors in the area of cost analysis as an element of the financial statement in an enterprise. Empirical studies were conducted on the basis of the financial statements published by selected companies listed on the NewConnect market in 2017, as well as the audit reports issued for those companies. The partial goals include the assessment of the percentage of certain types of opinions issued by independent auditors reviewing the financial statements of selected companies listed, as well as the identification of the areas regarding costs of activities, which are most often described in the explanations or qualified opinions in the research sample under analysis. The undertaken research are preliminary and in the future should be carried out on a larger research sample divided into industry sectors(original abstract)